METHODOLOGICAL BASIS OF STUDYING CULTURAL DIALOGUE IN THE CONTEXT OF INTERPRETATION OF THE ORIENTAL TRADITION IN RUSSIAN LITERATURE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article examines topical problems of studying Russian literature in the context of "dialogue of cultures" (Russian national culture with the East); methodological recommendations are given for improving the content of literary education in the upbringing of patriotic, international feelings of students, respect for traditions and the spiritual and aesthetic heritage of the East people.